Nuclear Performance of a Cylindrical Fission Ionization Chamber - QIU Shunli;GE Mengtuan;XIAO Wei;DONG Jincheng;ZHOU Yulin;SUN Guangzhi;ZENG Le;LIU Haifeng;PEI Yu;CHENG Hui (Journal of Isotopes, 2023)
In order to overcome the difficulties of meeting the engineering application requirements of the technical performance indicators of the fission ionization chamber, to explore the feasibility of the development of the longsensitive zone fission ionization chamber in actual application, and to realize the domestic application of the intermediate range detector for the excore nuclear instrumentation system (NIS) in the third-generation nuclear power plant, a cylindrical fission ionization chamber for the nuclear power plant external nuclear measurement system was developed. Based on the thermal neutron fluence standard device, standard γ radiation device and reactor irradiation hole test platform, the identification characteristics, thermal neutron sensitivity, charge per pulse, average electron collection time, high voltage plateau characteristics, repeatability and γ sensitivity of the fission ionization chamber were tested, and the relationship between the detector performance and temperature was tested. The test results show that the thermal neutron sensitivity of the fission ionization chamber can reach 0.53 s-1/nv, the charge per pulse is 1.88×10-13 C, the average electron collection time is 400 ns, the high voltage platform characteristics platform length ≥400 V, platform slope ≤4%/100 V, γ sensitivity 3.30×10-9 A·Gy-1·h, repeatability maximum value 2.4%, all indicators are better than the design requirements. The successful development of the fission ionization chamber lays a solid foundation for the subsequent development of the long-sensitive zone fission ionization chamber.